Prostitution, modernity, and the making of the Cuban Republic, 1840-1920 - Sippial, Tiffany A. (Envisioning Cuba., 2013)
Between 1840 and 1920, Cuba abolished slavery, fought two wars of independence, and was occupied by the United States before finally becoming an independent republic. The author argues that during this tumultuous era, Cuba's struggle to define itself as a modern nation found focus in the social and sexual anxieties surrounding prostitution and its regulation. This book shows how prostitution became a prism through which Cuba's hopes and fears were refracted. Widespread debate about prostitution created a forum in which issues of public morality, urbanity, modernity, and national identity were discussed with consequences not only for the capital city of Havana, but also for the entire Cuban nation.